Professional Microsoft SQL server 2008 programming - Vieira, Robert (Wrox professional guides., 2009)
Master the increasingly complex feature set of the latest release of Microsoft SQL Server with the information in Professional Microsoft SQL Server 2008 Programming . Review the new features of SQL Server that will be of interest to you as an experi.